Nox2+ myeloid cells drive vascular inflammation and endothelial dysfunction in heart failure after myocardial infarction via angiotensin II receptor type 1. (25th November 2020) - Molitor, M; Rudi, W.S; Garlapati, V.S; Finger, S; Wild, J; Knopp, T; Karbach, S; Ruf, W; Muenzel, T; Wenzel, P
Abstract: Background: Ischemic heart failure (HF) ensuing myocardial infarction (MI) leads to impaired left ventricular function, reduced cardiac output and counterregulatory activation of angiotensin II (AngII) levels. Furthermore, it is characterized by the initiation of a systemic inflammatory response. Objective: We aimed to elucidate the impact of myelomonocytic cells and their activation by angiotensin II on vascular endothelial function in a mouse model of HF after MI. Results: HF was induced in male C57BL/6J mice by permanent ligation of the left anterior descending coronary artery. Compared to sham, HF mice had significantly impaired endothelial function accompanied by enhanced mobilization of Sca-1+c-Kit+ hematopoietic stem cells and Sca-1-c-Kit+ common myeloid and granulocyte-macrophage progenitors in the bone marrow as well as increased vascular infiltration of CD11b+Ly6G-Ly6Chigh monocytes and accumulation of CD11b+ F4/80+ macrophages, assessed by flow cytometry. Using mice with Cre-inducible expression of diphtheria toxin receptor in myeloid cells, we selectively depleted lysozyme M+ myelomonocytic cells for 10 d starting 28d after MI. While the cardiac phenotype remained unaltered until 38d post MI, myeloid cell depletion attenuated vascular accumulation of Nox2+CD45+ cells, endothelial dysfunction, oxidative stress and vascular expression of adhesion molecules and angiotensin II receptor type 1 (AT1R). Pharmacological blockade of this receptor for 4 weeks did not significantly alter cardiac function, but mimicked the effects of myeloid cell depletion: Telmisartan (20 mg/kg/d, fed to C57BL/6J mice) diminished bone marrow myelopoesis and myeloid ROS production, attenuated endothelial leukocyte rolling and vascular accumulation of CD11b+Ly6G-Ly6Chigh monocytes and macrophages, resulting in improved vascular function with less abundance of Nox2+CD45+ cells. Conclusion: Endothelial dysfunction in HF ensuing MI is mediated by inflammatory Nox2+ myeloid cells infiltrating the vessel wall that can be targeted by AT1R blockade. Funding Acknowledgement: Type of funding source: None